Valeriana gaimanensis (Valerianaceae nom. conserv.), a New Species from the Patagonian Semi-Arid Desert, Argentina - Nagahama, Nicolas; Bach, Hernán Gerónimo; Manifesto, Maria Marcela; Fortunato, Renee Hersilia (American Society of Plant Taxonomists, 2019)
Valeriana gaimanensis, a new species from Argentinean Patagonia, is described and illustrated. The new species belongs to the subgenus Valeriana and is apparently endemic to the Extra-Andean Patagonia region, where it grows in an extremely arid environment, in contrast to most Valeriana species distributed in Patagonia. The morphological relationships of V. gaimanensis are discussed in comparison with V. carnosa, which resembles the new species morphologically. Principal component analysis was performed with 28 morphological variables, including specimens of these two species, revealing differences between them. This study provides the distribution, habitat, phenology, and etymology of V. gaimanensis, as well as a key separating it from the other Valeriana species that inhabit Extra-Andean Patagonia.